Pengaruh CR dan NPM terhadap ROA dengan DER sebagai Moderasi pada Perusahaan Makanan BEI 2020-2024 - Amaliatul Khasanah; Maretha Ika Prajawati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research is driven by the influence of financial ratios on profitability levels in manufacturing companies in the food subsector. The primary objective of this study is to analyze the impact of the CR and NPM on ROA, with the DER acting as a moderating variable that has the potential to strengthen or enhance this relationship in food companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The applied method is quantitative, with a purposive sampling technique utilizing data from annual financial reports. The research sample includes 20 companies in the food subsector, selected based on certain criteria. The research findings indicate that the CR has no significant effect on ROA, and DER also has no significant impact on CR or NPM. Conversely, DER has a significant positive effect on ROA, and NPM also shows a significant positive effect on ROA. These results emphasize the crucial role of effective debt management and increasing NPM as key elements in improving the profitability and financial performance of food companies in Indonesia.